Adaptasi Komunikasi Antarbudaya Mahasiswa Perantau Universitas Pembangunan Nasional Veteran Jakarta Asal Medan - Josephine Ester Angginauli Sihite; Retno Dyah Kusumastuti; Ratu Laura MBP (Brand Communication, 2022)
This research was conducted with the aim of knowing how to adapt and what obstacles were experienced by UPNVJ immigrant students from Medan. This research uses accommodation communication theory as a supporter in this research. The method used in this research is qualitative with the constructivism paradigm. The research approach in this study is phenomenology which is carried out to explore and understand the experiences of the immigrant students towards their adaptation activities. The data sources in this study are divided into two, namely primary data sources, namely six overseas students and secondary data sources, namely sources used by researchers to obtain additional data. The data collection technique used in this study was semi-structured interviews. Researchers used several stages of data analysis, namely data reduction, data presentation, conclusion drawing and data verification. The final result of this research shows that the overseas students from Medan have their own perspective on communication made by the people of Jakarta. Likewise, the way of communication carried out by nomad students with the community in their area of origin, there is more than one way. There are various obstacles experienced by overseas students when communicating in Jakarta. However, there are also many ways that immigrant students use to overcome these obstacles. The overseas students go through several stages of the process when adapting intercultural communication. Communication accommodation also occurs in the event of adaptation of intercultural communication of these nomad students. Communication accommodation carried out by overseas students is convergence communication accommodation. Where the overseas students try to adapt their way of communicating in a way that is usually used by the people of Jakarta when carrying out their communication